Factors affecting respiratory vaccination in Oklahoma cow-calf operations - Harwell, Kristina; Hagerman, Amy D.; Raper, Kellie Curry; Shear, Hannah; Biggs, Rosslyn; Whitworth, Barry (Frontiers in Veterinary Science, 2025)
IntroductionRespiratory disease is a leading cause of death loss among US beef cattle operations and has significant lingering negative impacts on calf health, performance, and financial returns as they move through the supply chain. It can also negatively impact cowherd reproductive performance. Yet, a significant number of beef cattle operations have not adopted respiratory vaccination for calves or the breeding herd.MethodsThis analysis explores the potential reasons why some producers vaccinate their cattle and some do not, including how influential factors regarding vaccination adoption differ between calves and the breeding herd using Probit regression analysis.ResultsRegression results indicate that, for calves, the likelihood of respiratory vaccine adoption is most influenced by herd size and the use of other vaccines. Breeding herd vaccination decisions are more complex, influenced not by herd size but rather by disease knowledge and risk perception, producer education, and cost barriers.DiscussionHerd health management education efforts through veterinarians and extension services can use these results to better target respiratory vaccination information addressing some of these barriers, improving national cattle herd health.